2020
DOI: 10.1108/reps-11-2019-0150
|View full text |Cite
|
Sign up to set email alerts
|

Stock market development and economic growth in Tanzania: an ARDL and bound testing approach

Abstract: Purpose The purpose of this paper is to contribute to empirical evidence by recognizing the importance of stock markets in the financial system and consequently its causality to economic growth and vice versa. Design/methodology/approach The study used the autoregressive distribute lag model (ARDL) with bound testing procedures, the sample covered quarterly time-series data from 2001q1 to 2019q2 in Tanzania. Findings The results suggest that stock market development have both negative and positive causalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…Another study in africa by Kapaya (2020) on the causality of the stock market on economic growth using the ARDL approach. Secondary quarterly data was obtained covering 2001 to 2019 from Tanzania.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study in africa by Kapaya (2020) on the causality of the stock market on economic growth using the ARDL approach. Secondary quarterly data was obtained covering 2001 to 2019 from Tanzania.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This has cause most African countries to implement. Other empirical studies such as Shahbaz et al (2008), Asante et al (2011), Kapaya (2020) also believed that stock market impact economic growth. King and Levine (1993), Demirgue-Kunt and Maksimovic (1998), Levine, Loayza and Beck (2002), Ahmad and Malik (2009), Derk (2020), showed that broader, deeper financial markets are strongly associated with economic growth, Despite the numerous benefits associated with stock market, Singh (1997) believed that stock market do not impact economic growth but rather such a market hamper economic growth due to their susceptibility to market failure, which is often showed in the uncertain nature of stock market in many developing countries.…”
Section: Introductionmentioning
confidence: 95%
“…The majority of countries in Africa adopted financial sector reforms to liberalise their financial systems as well as to enhance their non-bank financial institutions and capital markets (Kapaya, 2020;Osaseri and Osamwonyi, 2019;Qamruzzaman and Wei, 2018;Naik and Padhi, 2015). The rationale behind the reforms was the desire to expand financial intermediation through non-bank financial institutions and stock markets so as achieve sustained economic growth.…”
Section: Background To Sadc Stock Marketsmentioning
confidence: 99%
“…These are stock market development-led economic growth, economic growth-led stock market hypothesis, the feedback effect and the neutrality hypothesis. Kapaya (2020) studied the causal relationship between stock markets and economic growth in Tanzania. The study applied the Autoregressive Distribute Lag Model (ARDL) with bound testing procedures.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation